Technological quality and yield of sugarcane grown under nitrogen doses via subsurface drip fertigation - Rhein, Andressa F. L.; Pincelli, Renata P.; Arantes, Marcel T.; Dellabiglia, William J. [UNESP]; Kolln, Oriel T.; Silva, Marcelo de A. [UNESP] (Univ Federal Campina Grande, 2016)
This study characterized the technological quality and yield of sugarcane cv. SP80-3280 under nitrogen doses via subsurface drip fertigation. Five treatments were established using N-fertilizer in the form of urea (0, 50, 100, 150 and 200 kg N ha(-1)), with four replicates, applied via subsurface drip fertigation. The technological quality (fiber% cane; Brix% juice; pol% juice, pol% cane; juice purity and total recoverable sugar - TRS), as well as yield of stalks and sugar were determined 381 days after the third harvest. The technological variables Brix%, pol% juice, purity% and TRS of sugarcane, cultivar SP80-3280, were altered by the application of nitrogen doses via subsurface drip fertigation, with significant reductions at the dose of 200 kg N ha(-1). Stalk and sugar yields increased linearly with the increment in nitrogen doses applied through subsurface drip fertigation.
Keywords: Saccharum spp.; nitrogen fertilization; full irrigation; pol% cane; yield